Strategi Penerjemahan Ujaran Makian Bahasa Prancis dalam Film Banlieue 13 Karya Pierre Morel - Noor Diana Arrasyid; Sajarwa Sajarwa; Wulan Tri Astuti (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to identify the strategies through which French-language profanity is translated into Indonesian by using a corpus of data drawn from the dialogues of the French film Banlieue 13 and its Indonesian subtitles. The data were collected through certain steps started with watching the film, noting each use of French-language profanity and its Indonesian translation, then classifying those data based on Davoodi's proposed categories of profanity translation strategies. This study finds that four strategies were used for translating French profanity to Indonesian: censorship (as in the term 'bordel', which was left untranslated), substitution (as in the term 'putain', translated as 'astaga'), taboo (as in the term 'merde', translated as 'sial'), and also euphemism (as in the term 'merde', translated as 'hal buruk'). Furthermore, the result shows that both French and Indonesian language profanity is often used in reference to situations and occupations considered taboo in society.